Croatian young learners of English and non-core pronunciation features - Josipović Smojver, Višnja (2013)
Recent studies on ELF in Croatia have dealt with the attitudes of learners and teachers at all levels of education. Within the framework of a project on early acquisition of English as a foreign language, the English pronunciation feature s of 26 Croatian primary-school pupils were analysed in light of the emergence of English as a global language. Typical violations of the ELF core features, as defined by Jenkins (2002), were diagnosed, and the insights gained were meant to raise the awareness towards the international intelligibility of ELF users. Profiles of more and less successful young learners of English pronunciation were drawn and learners’ success in acquiring English pronunciation was related to extralinguistic factors. The presentation focuses on non-core native-like pronunciation features not crucial for international intelligibility. Findings show that they tend to be associated with successful learners. Success in mastering the core goes hand in hand with acquiring native-like non-core features which are then perceived as part and parcel of what is generally felt to be 'good English'. Moreover, the absence of features such as vowel reduction, stress-based rhythm, clear vs. dark /l/ alternation, or approximant /r/ realisation seems to be instrumental in the creation of the cumulative effect of a foreign accent, which at some critical point may be felt as comical. When it becomes too obtrusive, even if perfectly internationally intelligible, a foreign accent may draw too much attention to itself and thus detract from the effectiveness of the intended message. Data were collected from 26 children chosen by their teachers as representatives of poor, average and high learning ability. Findings are based on analyses of observation and interview data collected over a period of four years and rated by two independent raters.